Global performance enhancements via pedestal optimisation on ASDEX Upgrade. (20th December 2016) - Dunne, M G; Frassinetti, L; Beurskens, M N A; Cavedon, M; Fietz, S; Fischer, R; Giannone, L; Huijsmans, G T A; Kurzan, B; Laggner, F; McCarthy, P J; McDermott, R M; et al.
Abstract: Results of experimental scans of heating power, plasma shape, and nitrogen content are presented, with a focus on global performance and pedestal alteration. In detailed scans at low triangularity, it is shown that the increase in stored energy due to nitrogen seeding stems from the pedestal. It is also shown that the confinement increase is driven through the temperature pedestal at the three heating power levels studied. In a triangularity scan, an orthogonal effect of shaping and seeding is observed, where increased plasma triangularity increases the pedestal density, while impurity seeding (carbon and nitrogen) increases the pedestal temperature in addition to this effect. Modelling of these effects was also undertaken, with interpretive and predictive models being employed. The interpretive analysis shows a general agreement of the experimental pedestals in separate power, shaping, and seeding scans with peeling-ballooning theory. Predictive analysis was used to isolate the individual effects, showing that the trends of additional heating power and increased triangularity can be recoverd. However, a simple change of the effective charge in the plasma cannot explain the observed levels of confinement improvement in the present models.